Modifikasi Permukaan Kayu Pinus Menggunakan Metode Finishing Tradisional Jepang – Yakisugi pada Beberapa Level Pengarangan - Fahrussiam, Fauzan; Lestari, Andi Tri; Chaerani, Nurul; Lestari, Dini (PERENNIAL, 2023)
The yakisugi is a japan method on wood finishing that enhances an esthetic, dimension stability and durability. Yakisugi methode traditionally carried out by tying three boards together to form an elongated triangle and then burning until black charcoal is evenly created on the wood surface. Thes method has not been extensively researched or industrialized in Indonesia. Therefore, this study aims to evaluate the quality of yakisugi finishing on pine wood with parameters such as the length of the burning process (20 seconds and 30 seconds on a 70 cm2 area). The results showed that the pine wood burning process produced higher dimensional stability than pine without burning treatment, with ASE values reaching about 56% at a burning time of 30''.  Meanwhile, in the mechanical properties test, the yakisugi method provides lower values of MOE and MOR than the control sample—the change in wood properties to become more brittle after combustion is the main reason for this phenomenon. The combustion characteristics show that the combustion duration does not give a different color change in the test sample after the charcoal cleaning process. However, the thickness of the charcoal produced at 30" showed a higher value of 4.5 mm.